2023
DOI: 10.3389/fmolb.2023.1180537
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling reveals altered tryptophan metabolism in patients with kawasaki disease

Abstract: Kawasaki disease (KD) is a childhood vasculitis disease that is difficult to diagnose, and there is an urgent need for the identification of accurate and specific biomarkers. Here, we aimed to investigate metabolic alterations in patients with KD to determine novel diagnostic and prognostic biomarkers for KD. To this end, we performed untargeted metabolomics and found that several metabolic pathways were significantly enriched, including amino acid, lipid, and tryptophan metabolism, the latter of which we focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Lim et al 18 showed that KP metabolites in the serum of patients with multiple sclerosis may have applications as disease biomarkers. The increased levels of KYN and KYNA have been postulated as novel diagnostic biomarkers for Kawasaki disease in children 51 . Park et al 24 suggested that serum KYN/TRP ratio can be a potential biomarker of fatigue in the primary Sjögren's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al 18 showed that KP metabolites in the serum of patients with multiple sclerosis may have applications as disease biomarkers. The increased levels of KYN and KYNA have been postulated as novel diagnostic biomarkers for Kawasaki disease in children 51 . Park et al 24 suggested that serum KYN/TRP ratio can be a potential biomarker of fatigue in the primary Sjögren's syndrome.…”
Section: Discussionmentioning
confidence: 99%